Diagnostic Validity of Cardiopulmonary Exercise Testing for Screening Pulmonary Hypertension in Patients With Chronic Obstructive Pulmonary Disease. Issue 3 (May 2020) - Kader, Mohamed Nabhan; Moiz, Jamal Ali; Bhati, Pooja; Ali, Mir Shad; Talwar, Deepak
Abstract : Purpose: To determine diagnostic validity of cardiopulmonary exercise testing (CPX) parameters for detecting pulmonary hypertension (PH) in patients with chronic obstructive pulmonary disease (COPD) and to investigate association between CPX parameters and indices of PH. Methods: This cross-sectional study enrolled 48 moderate to very severe COPD patients in whom PH was confirmed by echocardiography. Symptom-limited CPX was performed using an incremental exercise protocol. Relevant CPX parameters were derived and were tested for their diagnostic ability for diagnosing PH. Logistic regression was applied to examine the effect of various clinical covariates on the diagnostic ability of exercise test variables for detecting PH. Results: Of the 48 patients, 29 were diagnosed with PH and 19 were negative for PH based on echocardiographic testing. CPX measures including peak oxygen uptake (% predicted O2peak, O2peak [mL/min], O2 /kg), oxygen pulse ( O2 /HR % predicted, O2 /HR mL/beat), and peak minute ventilation ( Epeak [L/m]) were inversely correlated with mean pulmonary arterial pressure (mPAP). Peak O2 /HR and O2peak were found to be significant predictors of PH in univariate analysis. O2peak (%), O2 /HR (mL/beat), and desaturation (%) were identified as independent predictors of PH adjusted for age, forced expiratory volume in 1 sec (%), and forced vital capacity (L). Conclusion: The present study validates the use of CPX parameters such as O2peak and O2 /HR as a diagnostic tool for correctly identifying PH in COPD patients. Therefore, CPX may be used as an adjunct to echocardiographic measurement of PH where there is unavailability of equipment and expertise. Abstract : The present investigation intended to investigate determine the diagnostic ability of cardiopulmonary exercise testing parameters for detecting pulmonary hypertension (PH) in patients with chronic obstructive pulmonary disease (COPD) patients. Peak oxygen uptake and oxygen pulse were independent predictors of PH in COPD patients.